Energy and exergy analyses of R513a as a R134a drop-in replacement in a vapor compression refrigeration system. (April 2020) - Sun, Jian; Li, Wenhua; Cui, Borui
Highlights: The energy and exergy performance of R513a as a drop-in replacement for R134a in a refrigeration system is investigated. The contributions of the individual components to the exergy destruction rate increase have been identified. A system with drop-in R513a demonstrates reduced capacity and efficiency under a majority of operating conditions. The compressor was the largest contributor to the irreversibility when R513a was used as a drop-in replacement for R134a. Abstract: R513a (XP10), a mixer of 56% R1234yf (C3 H2 F4 ) and 44% R134a (CH2 FCF3 ), has similar thermophysical characteristics to R134a but only half of its global warming potential (GWP). This paper uses an economized-cycle vaper compression refrigeration system as an example to investigate the energy and exergy performance of R513a used as a drop-in replacement for R134a. Differing from previous research, this study examines the entire system operating zone to identify the performance differences in terms of capacity, COP, exergy destruction rate, and exergy efficiency between R513a and R134a systems. The analysis found that a system with drop-in R513a demonstrates reduced capacity by up to 12% and efficiency (up to 9% with COP and 14% with exergy efficiency) under a majority of operating conditions, while exhibiting less irreversibility (5% to 13%) under high-ambient, high-space temperature conditions and better exergy efficiency of 3% in low-ambient conditions. In addition, the contribution of each individual component to the exergy destruction rate at various operating conditions is identified. To improve the energy and exergy efficiency of a R513a system, the analysis results indicate that the compressor is the first component that should be redesigned or reselected, followed by the economizer, valves, and evaporator. The condenser influence is negligible.